The Immune Microenvironment in Mesothelioma: Mechanisms of Resistance to Immunotherapy - Chu, Gerard J.; van Zandwijk, Nico; Rasko, John E. J. (Frontiers in Oncology, 2019)
Although mesothelioma is the consequences of a protracted immune response to asbestos fibres and characterized by a clear immune infiltrate, novel immunotherapy approaches show less convincing results as seen in melanoma and non-small cell lung cancer. The immune suppressive microenvironment in mesothelioma is likely contributing to this therapy resistance. Therefore, it is important to explore the characteristics of the tumour microenvironment for explanations for this recalcitrant behavior. This review describes the stromal, cytokine, metabolic and cellular milieu of mesothelioma, and attempts to make connection with the outcome of immunotherapy trials.